The Basic Foundations of Parental and Child Rights in Islam: A Perspective Study of QS. Al-Isra Verses 23-24 - Puspita Ais Anggraini; Noorazmah Hidayati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The relationship between parents and children is an important aspect in Islam as emphasized in the QS. Al-Isra Verses 23-24. This verse provides guidance regarding children's obligations to be filial to their parents, especially when they enter old age. This research aims to analyze the rights between parents and children from an Islamic perspective using a qualitative approach with a literature study on the interpretation of the Al-Qur'an. The results of the study show that filial piety to parents is an obligation that is parallel to the command to worship Allah, including respect, affection and good treatment, without saying or showing rude behavior. Islam also emphasizes a balance of rights, where parents have the right to be respected and cared for, while children have the right to education, love and protection. This study confirms that QS. Al-Isra Verses 23-24 are the foundation for family harmony, especially amidst the challenges of the modern era.